Growth performance, bone mineralization, nutrient digestibility, and fecal microbial composition of multi-enzyme-supplemented low-nutrient diets for growing-finishing pigs. (22nd March 2022) - Hong, Jinsu; Jlali, Maamer; Cozannet, Pierre; Preynat, Aurelie; Adams, Seidu; Scaria, Joy; Woyengo, Tofuko A
Abstract: A study evaluated the effects of adding multi-enzyme mixture to diets deficient in net energy (NE), standardized ileal digestible (SID) amino acids (AA), standardized total tract digestible (STTD) P, and Ca on growth performance, bone mineralization, nutrient digestibility, and fecal microbial composition of grow-finish pigs. A total of 300 pigs (initial body weight [BW] = 29.2 kg) were housed by sex and BW in 45 pens of 7 or 6 pigs and fed 5 diets in a randomized complete block design. Diets were positive control (PC), and negative control 1 (NC1) or negative control 2 (NC2) without or with multi-enzyme mixture. The multi-enzyme mixture supplied at least 1, 800, 1, 244, 6, 600, and 1, 000 units of xylanase, β -glucanase, arabinofuranosidase, and phytase per kilogram of diet, respectively. The PC was adequate in all nutrients. The NC1 diet had lower content NE, SID AA, STTD P, and Ca than PC diet by about 7%, 7%, 32%, and 13%, respectively. The NC2 diet had lower NE, SID AA, STTD P, and Ca than PC diet by 7%, 7%, 50%, and 22%, respectively. The diets were fed in four phases based on BW: Phase 1: 29–45 kg, Phase 2: 45–70 kg, Phase 3: 70–90 kg, and Phase 4: 90–120 kg. Nutrient digestibility, bone mineralization, and fecal microbial composition were determined at the end of Phase 1. Pigs fed PC diet had greater ( P < 0.05) overall G:F than those fed NC1 diet or NC2 diet. Multi-enzyme mixture increased ( P < 0.05) overall G:F, but the G:F of the multi-enzyme mixture-supplemented diets did not reach ( P < 0.05) that of PC diet. Multi-enzyme mixture tended to increase ( P = 0.08) femur breaking strength. Multi-enzyme mixture increased ( P < 0.05) the ATTD of GE for the NC2 diet, but unaffected the ATTD of GE for the NC1 diet. Multi-enzyme mixture decreased ( P < 0.05) the relative abundance of the Cyanobacteria and increased ( P < 0.05) relative abundance of Butyricicoccus in feces. Thus, the NE, SID AA, STTD P, and Ca could be lowered by about 7%, 7%, 49%, and 22%, respectively, in multi-enzyme mixture-supplemented diets without negative effects on bone mineralization of grow-finish pigs. However, multi-enzyme mixture supplementation may not fully restore G:F of the grow-finish pigs fed diets that have lower NE and SID AA contents than recommended by 7%. Since an increase in content of Butyricicoccus in intestine is associated with improved gut health, addition of the multi-enzyme mixture in diets for pigs can additionally improve their gut health. Lay Summary: A study evaluated the effects of supplementing a multi-enzyme mixture that contain fiber degrading enzymes and phytase on the growth performance, bone strength, and fecal microbial composition of grow-finish pigs fed corn-wheat-wheat bran-based diets. Five diets fed were a positive control (PC) diet, and two negative control (NC1 and NC2) diets without or with the multi-enzyme mixture. The PC diet was adequate in all nutrients and had greater available (net) energy and digestible amino content than NC1 diet or NC2 diet by 7%, and greater digestible P content than the NC1 diet (by 32%) and NC2 diet (by 50%). The diets were fed from 30 to 120 kg body weight. Feed efficiency for PC diet was greater than that for NC1 diet or NC2 diet. Multi-enzyme mixture improved feed efficiency, bone strength, and fecal concentration of beneficial micro-organisms (known as Butyricicoccus ) for NC1 and NC2 diets. However, feed efficiency for the NC1 and NC2 diets did not reach that for the PC diet. Thus, multi-enzyme mixture can fully restore bone strength (but not feed efficiency) and improve health of grow-finish pigs fed corn-wheat-wheat bran-based diets in which available energy, amino acids, and P contents have been reduced by the afore-mentioned margins. Abstract : Supplementation of corn-wheat-wheat bran-based diets that are deficient in net energy and digestible amino acids and P with multi-enzyme mixture can result in improved feed efficiency, bone mineralization, energy and nutrient digestibility; and increased fecal concentration of Butyricicoccus microorganisms (that are beneficial with regard to gut health) of grow-finish pigs.